Abdominal pain in late pregnancy (≥24 weeks' gestation). Issue 7 (July 2022) - Odubamowo, Kehinde H.; Chilaka, Chioma; Walker, Kate F.
Abstract: Abdominal pain in late pregnancy is a common presentation and can pose a diagnostic and management dilemma to clinicians. For this article we have defined late pregnancy as ≥ 24 weeks gestation. An acute abdomen affects 1 in 500 pregnancies with approximately 0.5–2% of pregnant women needing surgical interventions in pregnancy. The majority of acute abdominal complaints will present in a similar manner to the non-pregnant patient; however the anatomical and physiological changes of pregnancy can complicate the diagnosis and management options. Appendicitis remains the most common cause of an acute abdomen in pregnancy. Management should be tailored depending on the patient and the severity of the condition. Special consideration should be made for the fetus but the life of the mother should be of primary concern. Surgery can therefore be performed at any stage of pregnancy if, on balance, it is the most appropriate option. Clinicians should not neglect obstetric causes of pain and endeavour to always diagnose the underlying cause of the abdominal pain to aid management. This article explores the different aetiologies of pain in late pregnancy and latest advances in management.